Uji Daya Antiinflamasi Ekstrak Etanol Daun Mangkokan (Nothopanax Scutellarium Merr.) pada Mencit Yang Diinduksi Karagenin - Tia Intan Pradita; Sri Rejeki (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Mangkokan leaves (Nothopanax scutellarium Merr.) contain flavonoids, alkaloids, saponins, and polyphenols which are used to treat wounds, antibacterial, anti-inflammatory, and antioxidants. This study aims to determine the ethanol extract of mangkokan leaves has anti-inflammatory power in mice induced by carrageenan and to determine the effective dose of mangkokan leaf ethanol extract which provides anti-inflammatory power comparable to the positive control. This type of research is experimental. Mangkokan leaves were extracted by maceration method using 70% ethanol solvent. The test animals used were 25 mice and divided into 5 groups. All groups were induced with carrageenan. Group I was given positive control (na diclofenac), group II was given negative control (coconut oil), and groups III, IV, V were given ethanol extract of mangkokan leaves each with a dose of 100 mg / kg, 200 mg / kg, 400 mg / kgBB. The results of measuring the length of edema every 30 minutes for 6 hours were analyzed with the help of SPSS version 22.0 for windows. Results% DAI of the ethanol extract of mangkokan leaves with a dose of 400 mg was 58.88%, a dose of 200 mg was 50.49%, a dose of 100 mg was 43.67%, and a positive control was 66.71%. The conclusion of this study is that the ethanol extract of mangkokan leavesÂ anti-inflammatory activity in mice which is comparable to the positive control with a dose of 400 mg.The ethanol extract of mangkokan leaves has the potential to be anti-inflammatory.